Risiko Terjadinya Tindak Pidana Pencucian Uang Melalui Pasar Modal - Talitha Rahma; Elvia Elvaretta; Dominikus Rato; Fendi Setyawan (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Capital markets, namely activities related to the offering and trading of company assets. In transactions in the capital market, several features of financial transactions are carried out quickly, adaptively and cross-border, allowing the capital market to be used as a means and medium for laundering money from illegal funds. The capital market can be said to be a unique financial sector compared to other financial services sectors. This is because the capital market can be used to launder illegal funds obtained from a criminal act which are then used to generate legitimate profits through fraudulent activities.